Synthesis and characterization of(Oxazepine,Diazepine,Terazole) for Derivatives of 2 ـ aminobenzolthiazd Derivatives (Journal of the College of Basic Education, 2022)
The present work involved synthesis of serval new substituted (oxazepine, Diazepine and tetrazole via Schiff bases for 2-aminobenzothiazole derivatives by five steps. The first step involved preparation 2-aminobethiazole (1-4) by thiocyanogen method in the presence of a suitable solvent, the second step involved preparation Schiff Bases (1-4) by condensation of 2-aminobenzothiazole derivatives with many substituted aldehydes , then, the third step include, preparation new four oxapezine compounds (5-12) by reaction of phthalic anhydride and malic anhydride with the prepared Schiff Bases in two step. the fourth including reaction compounds (5-12) which prepared in the third step with primary oramatic amines to give new eight Diazepine compounds (13-20). Finally the fifth step, preparation new tetrazole derivatives (21-24) by reaction of the prepared Schiff Bases (in the second step) with sodium azide in THf. The prepared compounds were characterized by physical properties, FT-IR, UV. And some of them by 1H-NMR, 13C-NMR spectroscopy were recorded.